2022
DOI: 10.3389/fncel.2022.997360
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic plasticity in two cell types of central amygdala for regulation of emotion and pain

Abstract: The amygdala is a critical brain site for regulation of emotion-associated behaviors such as pain and anxiety. Recent studies suggest that differential cell types and synaptic circuits within the amygdala complex mediate interacting and opposing effects on emotion and pain. However, the underlying cellular and circuit mechanisms are poorly understood at present. Here we used optogenetics combined with electrophysiological analysis of synaptic inputs to investigate pain-induced synaptic plasticity within the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Significantly, patients suffering from HNSCC often experience depressive disorders, which are poorly managed clinically [84][85][86] . Here, we found that nociceptor neurons infiltrating HNSCC connect to a preexisting brain-projecting circuit 87,88 that includes the trigeminal ganglia, the spinal nucleus of the trigeminal (SpVc), as well as the parabrachial nucleus (PBN), and central amygdala (CeA) [89][90][91][92] .…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, patients suffering from HNSCC often experience depressive disorders, which are poorly managed clinically [84][85][86] . Here, we found that nociceptor neurons infiltrating HNSCC connect to a preexisting brain-projecting circuit 87,88 that includes the trigeminal ganglia, the spinal nucleus of the trigeminal (SpVc), as well as the parabrachial nucleus (PBN), and central amygdala (CeA) [89][90][91][92] .…”
Section: Discussionmentioning
confidence: 99%
“…The open field test was conducted in an illuminated chamber (72 × 72 × 50 cm) divided by a central zone and an outer zone as we described before ( Cai et al, 2018 ; Ge et al, 2022 ). A rat was connected to the light source and was placed in the center of the chamber.…”
Section: Methodsmentioning
confidence: 99%
“…Opposite changes may lead to NP and memory deficits, respectively ( Liu et al, 2017 ). The amygdala, ACC, and other key brain nuclei for sensing emotion-related behaviors such as pain and anxiety are also highly plastic ( Zhuo, 2020 ; Ge et al, 2022 ). Thus, modulating structural or functional plasticity in brain synapses can inhibit central sensitization and thus reduce NP.…”
Section: Brain Mechanisms Involved In the Treatment Of Np By Using Ac...mentioning
confidence: 99%